Penerapan Quality Function Deployment (QFD) Pada Desain Smart Aquaculture Untuk Sektor Tambak Udang Vaname Berbasis IOT - Budi Setiawan; Nico Surantha (Journal of Information System Research (JOSH), 2023)
In entering the era of industry 4.0. where the internet world has the main role as a link to every device to collect and analyze data. Internet Of Things (IOT) technology can optimize previous technologies. In the fishing industry, Indonesia has the potential for fishery land in 2020 of 1,201,275 ha. The large area of water area in Indonesia has potential for aquaculture such as vannamei shrimp. Water quality such as pH, turbidity level and shrimp feeding schedule in ponds are closely related to shrimp health conditions. The existence of good water quality management can maintain water quality in order to increase pond productivity. Technology and information integration through paired IOT sensors will transmit data collected in the field to cloud computing via internet-based radio frequency networks through virtualization. This study aims to design a realtime IOT-based shrimp pond monitoring system. The Quality Function Deployment (QFD) method is a method that aims to plan and develop products according to needs and desires of consumers. This method begins with making a matrix of consumer needs and desires for the cultivation of Vaname Shrimp ponds. From this data a House of Quality matrix will be created which contains any technical interests needed. For the evaluation results of the questionnaire based on the analysis of the answers given by the respondents, the questionnaire that has been made can be used as a reference so that the proposed system design can be realized to overcome Vaname Shrimp ponds in order to improve the quality and quantity of vannamei shrimp harvest, cultivate effectively and efficiently, and facilitating the supervision of pond managers on pond water quality, feeding and feed availability.